111k views
4 votes
F(x) = 8x – 3; g(x) = 4x + 5 find (f-g)(x)

User Camara
by
5.3k points

1 Answer

5 votes

Given:

The two functions are
f(x)=8x-3 and
g(x)=4x+5

We need to determine the value of the function
(f-g)(x)

The value of
(f-g)(x):

The value of
(f-g)(x) can be determined using the formula,


(f-g)(x)=f(x)-g(x)

Substituting the values of the function in the above formula, we get;


(f-g)(x)=8x-3-(4x+5)

Simplifying, we get;


(f-g)(x)=8x-3-4x-5

Adding the like terms, we get;


(f-g)(x)=4x-8

Thus, the value of the function
(f-g)(x) is
(f-g)(x)=4x-8

User Ian P
by
5.0k points